Grey correlation analysis of milling temperature and milling vibration of TC4 titanium alloy. (June 2022) - Li, Shuncai; Hu, Yuting; Popov, Eugene
In this paper, a synchronous acquisition system of milling temperature and milling vibration was established to measure the data of milling temperature and milling vibration. Based on grey correlation theory, the influence of milling parameters and milling vibration on milling temperature was analyzed. It is found that the grey correlation degree between milling temperature and milling parameters and vibration is above 0.70, indicating that milling parameters and vibration have great influence on temperature. In addition, the GM (0, N) grey prediction model of milling temperature on milling parameters and milling vibration was established, and the correlation coefficient of the model was above 0.8, indicating that the reliability of the model was high, and the correlation between milling temperature and milling vibration signal was high.